2018
DOI: 10.1002/cam4.1832
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of circulating tumor cells in head and neck and non‐small‐cell lung cancer

Abstract: Tumor biopsy is the gold standard for the assessment of clinical biomarkers for treatment. However, tumors change dynamically in response to therapy, and there remains a need for a more representative biomarker that can be assayed over the course of treatment. Circulating tumor cells (CTCs) may provide clinically important and comprehensive tumoral information that is predictive of treatment response and outcome. Blood samples were processed for CTCs from 56 patients using the ClearCell FX system. Captured cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 54 publications
2
87
0
Order By: Relevance
“…The results of the present study are in accordance with other studies investigating CTCs in solid cancers, including the head and neck, which revealed that the presence of CTCs may influence prognosis (11)(12)(13)(14)(15)(16)(17)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57) similar to what was observed in the patients in the present study (6/8 were positive to CTC preoperatively). A recent meta-analysis comprised of 17 studies confirmed the significant prognostic value of CTCs in patients with head and neck cancer, wherein positive CTCs were significantly associated with poor overall, disease-free and progression-free survival (61).…”
Section: Discussionsupporting
confidence: 92%
“…The results of the present study are in accordance with other studies investigating CTCs in solid cancers, including the head and neck, which revealed that the presence of CTCs may influence prognosis (11)(12)(13)(14)(15)(16)(17)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57) similar to what was observed in the patients in the present study (6/8 were positive to CTC preoperatively). A recent meta-analysis comprised of 17 studies confirmed the significant prognostic value of CTCs in patients with head and neck cancer, wherein positive CTCs were significantly associated with poor overall, disease-free and progression-free survival (61).…”
Section: Discussionsupporting
confidence: 92%
“…It is generally accepted that CTCs may play an important role in cancer metastasis . Data suggest that an elevated baseline CTC count is associated with advanced stage of HNSCC, risk of relpase, and a poor prognosis, while a declining CCRT could indicate an improved prognosis and treatment response . In some patients, an increased CTC count has been observed after HNSCC treatment by surgery and radiotherapy, which is thought to possibly reflect stimulation of tumor cell dissemination and a poorer prognosis; although, the exact reasons for this observation remain unclear.…”
Section: Biomarkers From Liquid Biopsiesmentioning
confidence: 99%
“…Previous research has shown that CTCs can also cause tumor recurrence and are related to patient prognosis . The ability to obtain more information from CTCs may therefore offer an avenue toward the early detection of cancer, allowing researchers to gain insight into its the aggressive nature of the tumor and offering a means of monitoring therapeutic responses and disease progression in patients …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, developing an assay not reliant upon EpCAM for effective capture and identification of additional subtypes of CTCs is imperative. Because chromosomal instability can cause aneuploidy in human solid tumor cells, an assay integrating EpCAM‐independent subtraction and immunostaining‐fluorescence in situ hybridization (FISH) has been reported in previous studies …”
Section: Introductionmentioning
confidence: 99%